Physical activity and the risk of malignant breast cancer development in women - Plagens-Rotman, Katarzyna; Chmaj-Wierzchowska, Karolina; Piskorz-Szymendera, Małgorzata; Zielińska, Aleksandra; Wilczak, Maciej; Pięta, Beata (Journal of Medical Science, 2017)
Introduction. The role of physical activity in preventive healthcare constitutes a subject matter of numerous research. In fact, it was proven that physical effort has an impact on lowering the risk of some neoplasms. Aim. The aim of the paper was to assess the influence of physical activity on the increase or a decrease of odds ratio for developing breast cancer in women. Material and Methods. The research included healthy women and women diagnosed with breast cancer on the basis of biopsy material or surgical intervention. The research involved 850 women, aged 21–84. Results. Increased physical effort during household duties and physical activity in patients with breast cancer presented as follows: 1102.61 MET (Metabolic Equivalent of Task) for passive rest, 3803.47 MET for household duties, and 1971.54 MET for physical activity. On the other hand, in subjects with no change in the breasts the study indicated the following results: 1024.05 MET for passive rest, 4150.97 MET for domestic activities and 1651.46 MET for sports activities. Conclusion. Medium and high physical activity associated with household duties decreases the risk of breast cancer development. In order to lower the risk of developing breast cancer in women, active lifestyle should be promoted in terms of physical effort within medium physical activity, i.e. 600–1500 MET.